Hubungan Pengetahuan Dan Dukungan Suami Dengan Kepatuhan Kunjungan Nifas Di Puskesmas Sidomulyo - Siska Putri; Nispi Yulyana; Ratna Dewi (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2023)
The main indicator is the maternal mortality rate that can be used to evaluate the effectiveness of a maternal health program (MMR). Husband's understanding and support affects postpartum visits.The purpose of this study was to investigate how maternal compliance with postpartum visits at the work area of Sidomulyo Health Center in Bengkulu City is related to knowledge and husband's support. The design of this study was analytical with a cross-sectional perspective. In 2021, Sidomulyo Health Center in Bengkulu City will receive 176 mothers with children over 42 days old. 62 mothers with children over 42 days old were selected for the sample. Purposive sampling was used as the sampling method. The chi-square statistical test was used in data analysis with univariate and bivariate models.The majority of women have little knowledge (51.6%),good knowledge (48.4%), the majority do not receive help (54.8%), the majority receive support (45.2%), majority non-compliant (56.5%), and majority compliant (43.5%), according to research results using univariate analysis. According to the study's bivariate statistical results, acquaintances have a p-value of 0.023 ± 0.05 and spousal support has a p-value of 0.000 ± 0.05 for each variable. Wherever they are tasked with helping more mothers get postpartum visits, Puskesmas looks for suggestions to further strengthen their role in promoting the benefits of postpartum visits